Serious complications of local anaesthesia for cataract surgery: a 1 year national survey in the United Kingdom - Eke, Tom (BMJ Group, 2007)
BACKGROUND: The techniques of sub‐Tenon's, topical and topical‐intracameral local anaesthesia (LA) have become common in routine practice. AIMS: This study aimed (i) to estimate the frequency of various LA techniques used in cataract surgery, (ii) to estimate the incidence of severe adverse events associated with each LA technique, and (iii) to document these adverse events. METHODS: This was a prospective, 13 month observational study of routine practice in the UK in 2002–2003. The British Ophthalmological Surveillance Unit sent a monthly mailing to UK ophthalmologists, asking for reports of “potentially sight‐threatening or life‐threatening complications of LA for cataract surgery”. Current LA practice was assessed by questionnaire. RESULTS: Cataract surgery comprised 4.1% general anaesthesia, 92.1% LA without sedation and 3.9% LA with sedation. Of the estimated 375 000 LAs 30.6% were peribulbar, 3.5% retrobulbar, 42.6% sub‐Tenon's, 1.7% sub‐conjunctival, 9.9% topical and 11.0% topical‐intracameral LA. “Potentially sight‐threatening complications” were mostly associated with retrobulbar and peribulbar techniques and “potentially life‐threatening” complications with all techniques except topical/intracameral LA. Eight neurological complications consistent with brainstem anaesthesia were reported: 7 with peribulbar or retrobulbar LA. Poisson regression analysis strongly indicated that rates vary with technique (p<0.001 for “potentially sight‐threatening” complications, p = 0.03 for “neurological” complications). Because of likely under‐reporting, further complications probably occurred during the survey period. CONCLUSIONS: This large survey found a lower rate of reported serious complications with sub‐Tenon's, topical and topical‐intracameral LA compared with retrobulbar and peribulbar techniques. These “newer” methods may be preferable for routine cataract surgery.